PEMANFAATAN JARINGAN WISP BERBASIS ROUTER UNTUK BERBAGI AKSES INTERNET ANTAR RUMAH WARGA - Mantri, Mantri Kromo; Rayza, Rayza Lintang; Julia, Julia Safitri; Anshori Anshori; Thoha Firdaus (CV. Denasya Smart Publisher, 2025)
The digital divide, resulting from economic limitations in accessing the internet, is a significant problem in many communities, including Pujorahayu Village. This research aims to design and implement a router-based Wireless Internet Service Provider (WISP) network as an affordable communal solution. The methodology employed is the Network Development Life Cycle (NDLC), which was applied to ten households utilizing TP-Link WR845N routers in WISP mode connected to a single primary internet source. The implementation results indicate that the WISP network successfully provides stable and economic internet access, while also positively fostering participation and a spirit of digital collaboration among residents. Nevertheless, several operational challenges were identified, such as limited signal range and potential bandwidth saturation during peak hours. Based on these findings, this research concludes that the solution is technically and socially viable. Further development of a bandwidth management system, the use of additional devices for coverage expansion, and the establishment of a transparent and sustainable communal management model are recommended. The implementation of this model can be replicated in other regions to support equitable internet access and strengthen digital inclusion on a national scale.